Modeling and Analysis of Vibration Amplitude Reduction in In-Wheel Electric Vehicle Using a Regenerative Tune Mass Damper (TMD) - Margiasih Liana; I Kadek Warjaya (Indonesian Journal of Engineering, Science and Technology, 2026)
This is a digest of the paper. One of the features of in-wheel electric vehicles is an increase in unsprung mass due to the integration of the motor into the wheel. It’s resulting in both increased vibration amplitude and reduced Vehicle comfort and stability. The purpose of this study is to model and analyze the reduction in vibration amplitude in the suspension system of in-wheel electric vehicles using an electromagnetic-based Regenerative Tuned Mass Damper (TMD). A dynamic model was developed using the quarter-car approach and transformed to state-space form for simulation in MATLAB. The parameters used were TMD masses of 5 to 15 kg with an increase of 1 kg, with road excitation testing conducted using a sinusoidal wave with an amplitude of 0.02 m and a frequency of 5 Hz. The results were then evaluated based on the Root Mean Square (RMS) value of vehicle unsprung mass acceleration as an indicator of vibration-damping performance. The results show that implementing TMD improves vibration attenuation compared to the baseline system, increasing vibration reduction from 16.97% to 18.81%. The system performs best at a TMD mass of around 8 kg, while achieves maximal damping effectiveness. However, increasing TMD mass beyond the ideal point decreases vibration attenuation efficacy, indicating a detuning impact between the TMD and the primary system. In contrast, the regenerative TMD generates electrical energy that increases with mass, with output power increasing from 5.04 W to 11.17 W. This study contributes to the development of adaptive suspension system designs to minimize the risk of failure at the in-wheel motor of electric vehicles while generating energy recovery.